Dinâmica do fósforo de sedimentos de uma pequena bacia hidrográfica de cabeceira - Schenato, Ricardo Bergamo (2009)
The pressure on the natural resources has being shown more intense in the last decades, increasing degradation of air, soil and water around the world. Among the substances related to the environmental impacts that containing phosphate is one of great importance, being original from industrial discharges, domestic uses, and agricultural. The last one contributes mainly through the excessive application of phosphate fertilizers. The soil use out of its capacity generates great amount of sediments that goes to rivers, lakes and seas. When that sediment carries with it great content of phosphorus, it can unchain the eutrophication process, that is characterized by the increase of nutrients in the aquatic system, leading to the decrease in the amount of dissolved oxygen in the water, what causes the death of several species. The present work was divided in two studies that aimed to determine the relationship of phosphorus from sediments dynamics in the process of water contamination in function of soil management and vegetable cover in a small watershed at city of Agudo Rio Grande do Sul State, Brazil. Were collected samples in three periods with different predominant soil uses. The sediment concentration was obtained by drying at 105ºC. The phosphorus dessorption was made by extraction with anion exchange resin on special recipients that allow control the redox conditions. Also, was realized the chemical fractionation of phosphorus from different sites of watershed. The concentration of suspended sediments on water curses is related with characteristics of rain and soil use, and the submission of the sediments to oxygen poor atmosphere favored the phosphorus dessorption. The bioavailable phosphorus and potential bioavailable phosphorus desorbed from sediments were incremented by antropic action. The phosphorus chemical fractionation is a good index of human action on aquatic source, being possible to determine the sediments origin from sub-basins under different antropization degrees.